Analysis of Emotional Regulation in Koe No Katachi - Agus Imam Adi Putra; Titis Setyabudi (Universitas Muhammadiyah Surakarta, 2025)
This descriptive qualitative research aims to identify the forms of emotion regulation of the main characters in the film Koe no Katachi (A Silent Voice) using Gross and John's (2003) Emotion Regulation Process Model, and to analyze their narrative representation through Chatman's (1978) Story and Discourse framework. The study employed the documentation method for data collection and Thematic Analysis for interpretation. This analysis involved Theory Operationalization and Initial Coding, where Gross and John's framework classified psychological forms and Chatman's framework categorized narrative structures. The research findings indicate that healing and successful emotional regulation must begin with adaptive antecedent-focused strategies. Narratively, the film critiques the suppression of expression driven by collectivist cultural norms and ideologically promotes emotional openness as an absolute prerequisite for achieving narrative New Equilibrium. This research contributes to providing an integrated reading between clinical psychology and cinematic studies. Practically, this study serves as a foundation for educators and counselors to utilize film as an educational medium in mental health literacy programs in schools.